NOTES FROM NARNIA (ON THE HUMAN BODY). Issue 52 (4th June 2019) - Baker, Samuel
Abstract : What is a human body? Some reasons are given for thinking that, in the primary case, it is a body that is both of and suitable to a rational animal.